Teacher's Written Corrective Feedback on Student's Translation Improvement - Kalsum; Maghdalena (Universitas Sulawesi Barat, 2019)
This research aims to investigate the teacher's written corrective feedback toward the students’ translation improvement. It is focused on the student's translation on lexical and grammatical mistakes in translating the source text into the target text. Translation is an activity that aims to facilitate the communication process by interpreting the information received in one language into another language. However, the mistakes while translating cannot be avoid by the translator or the students. The students are commonly done mistakes lexically and grammatically. To overcome the mistakes, the teacher will be a facilitator in correcting the student's translation. Implementing of written corrective feedback is provided teacher to correcting the student's mistakes by writing their comments, correction of errors, etc on the student's writing translation. Based on the analysis, the result indicates that the students make mistakes in translating, the students are most commonly made some mistakes in lexical and grammatical errors.